What is the direct cost of providing burn care at a burns unit in a tertiary care hospital in India? A health provider perspective - Frederick Satiro Vaz; Yuri Dias-Amborcar; Ritam Dessai; Archana Milind Desai; Sudeep Ramdas Lokapure (Discover Public Health)
Abstract Background Burns represent a major global public health concern, especially in low- and middle-income nations, where they cause high rates of morbidity and death as well as a large financial burden. More than a million Indians experience moderate-to-severe burns every year. Detailed, cost-focused research is lacking. This study fills this gap by calculating the direct costs of treating acute burn injuries in a government-run tertiary care environment. Methods In 2021, we retrospectively analyzed all acute burn patients hospitalized to a tertiary care hospital in Goa, India, and admitted to the Burns Unit. The research did not include capital or overhead expenditures; instead, it concentrated solely on direct costs, including drugs, medical supplies, investigative expenses, food, and staff pay. A bottoms-up methodology was used to assess costs, and hospital records provided the data. Microsoft Excel and Jamovi, an open-source program built on R, were used for statistical analysis. Results 121 individuals were included in the study, and their average hospital stay was 14.3 days, with a mean percentage of total body surface area (TBSA) burned of 21.2%. The total direct expenditures for the year came to ₹13,618,086 ($180,491 USD), with an average cost of ₹112,546 ($1,492 USD) per patient, an average daily cost of ₹7,845 ($104 USD) per patient, and an average cost of ₹5,303 ($70 USD) for each percentage point of TBSA burned. The biggest contributors to expenditure were staff salary and pharmaceuticals, accounting for 57.7% and 36.3% of the total spend, respectively. Conclusion The significant upfront expenses associated with acute burn care draw attention to the financial difficulties tertiary care hospitals in resource-constrained environments face. These results highlight the necessity of interventions to optimize resource allocation and save expenses without compromising the quality of service.